(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article examines the problem of normalizing the interaction between a teacher and parents of children with special educational needs on the basis of partnership pedagogy. Attention is focused on the specificity of the psychological state of a family raising a child with special educational needs as a prerequisite for complicating the cooperation of all members of the team of psychological and pedagogical support. An attempt is made to highlight the psychological aspects for harmonizing the partnership between parents and teachers in an inclusive educational environment.